Essentials of inventory management - Muller, Max 1947 (Harpercollins Leadership, 2019)
Beyond core tasks such as locating items, you've got to project future business needs, hold down costs, and fix supply chain problems. You need strategic and financial knowledge, and the skills to manage many moving parts. Essentials of Inventory Management is the answer book that practitioners and students rely on. It breaks down the job into easy concepts and concrete steps. New chapters in the third edition explain how to purchase inventory, pick the best location for a distribution center, and establish safety precautions for handling inventory. Maintaining physical spaces and databases are only part of your responsibilities. From forecasting to troubleshooting to the fundamentals of finance, this book gives you the tools to optimize efficiency--and drive profits. --